2005
DOI: 10.22358/jafs/67147/2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of transgenic maize Cry1Ab protein subjected to ruminal digestion

Abstract: This research determined the extent of ruminal degradation of a transgenic protein (Cry1Ab) expressed in kernels of maize (Zea mays) cultivar DKC53-32. Cracked kernels of transgenic maize (Bt+) were subjected to rumen digestion using in situ experiments with two ruminally cannulated Holstein cows. A non-transgenic maize cultivar (Bt-) was used as a control for crude protein (CP) degradation. CP and Cry1A concentrations from dacron polyester bags inserted in the rumen were determined for 48 h. The Bt-cultivar h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Some authors have studied the extent of Cry1A(b) protein degradation, using in situ experiments with ruminally cannulated cows. Using this technique, Jacobs et al determined that the amount of Cry1A(b) protein remaining after 16 and 24 h of ruminal degradation was 85% and 60%, respectively, indicating that a significant fraction of Cry1A(b) protein was not digested in the rumen. However, Wiedemann et al observed a higher degradation of Cry1A(b) protein in the rumen, as a decrease to 28% of the initial value was measured within 2 h, and to 2.6% within 48 h. The full-size protein was detected up to 8 h, and thereafter, only fragments of approximately 17 and 34 kDa were found.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have studied the extent of Cry1A(b) protein degradation, using in situ experiments with ruminally cannulated cows. Using this technique, Jacobs et al determined that the amount of Cry1A(b) protein remaining after 16 and 24 h of ruminal degradation was 85% and 60%, respectively, indicating that a significant fraction of Cry1A(b) protein was not digested in the rumen. However, Wiedemann et al observed a higher degradation of Cry1A(b) protein in the rumen, as a decrease to 28% of the initial value was measured within 2 h, and to 2.6% within 48 h. The full-size protein was detected up to 8 h, and thereafter, only fragments of approximately 17 and 34 kDa were found.…”
Section: Introductionmentioning
confidence: 99%